Pertumbuhan Tanaman Tomat (Solanum lycopersicum) dengan Media Abu Terbang (Fly Ash) dan Abu Dasar (Bottom Ash) - Vivin Andriani; Purity Sabila Ajiningrum; Ngadiani Ngadiani (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The use of fly ash and bottom ash as a plant medium can reduce waste from burning coal. The ash waste contains micro and macro nutrients that plants can use for growth. The ash contains the elements Na, K, Ca, Mg, Cu, Zn, and MN. This research aims to determine the effect of fly ash, bottom ash, and their combination on the growth of tomato plants (Solanum lycopersicum). This research used RAL (Completely Randomized Design) with 12 factors and 3 replications, namely k0 (negative control, not given anything), k1 (positive control, given urea fertilizer), a1 (400 g/polybag fly ash), a2 (800 g/polybag fly ash), a3 (1200 g/polybag fly ash), b1 (400 g/polybag base ash), b2 (800 g/polybag base ash), b3 (1200 g/polybag base ash), ab1 (200 g/polybag fly ash + 400 g/polybag fly ash), ab2 (400 g/polybag fly ash + 200 g/polybag fly ash), ab3 (600 g/polybag fly ash + 400 g/polybag fly ash), and ab4 (400 g/polybag fly ash + 600 g/polybag fly ash). The observation variable is the growth of tomato plants, including plant height, number of leaves, number of branches, stem diameter and wet weight. The results showed that there was an effect of using fly ash and bottom ash as a planting medium on the growth of tomato plants for 90 DAP in the AB4 treatment. The combination of 400 g/polybag fly ash + 600 g/polybag fly ash gave good results in plant height, number of leaves, number of branches, and fresh weight of tomato plants, but in terms of branch diameter, NPK treatment gave good results.